Teacher’s Nonverbal Communication in Teaching Learning Process at SMP Negeri 2 Robatal Sampang Madura - Wildona Zumam; Mahfud (LPPM STKIP PGRI Sidoarjo, 2020)
The teacher is not only used verbal communication but also used nonverbalcommunication, this study aims to investigate the teacher use nonverbalcommunication in teaching learning process and the teachers’ nonverbalcommunication effect on the classroom atmosphere at SMP Negeri 2 RobatalSampang Madura. The subject of the study is the teacher and the students. Theinstruments used to get the data were observation, interview and documentation.Observation was applied in order to know the use nonverbal communication inteaching learning process at SMP Negeri 2 Robatal Sampang and activity in theclassroom. Interviews were conducted to know the effect of nonverbalcommunication in teaching learning process at SMP Negeri 2 Robatal Sampang.The result of the shows that teachers’ nonverbal used in teaching learning processare hands, space and distance, touching and chronemics. Hands is nonverbal themost used by the teacher in teaching learning process, the manner of the usedhands in teaching learning process , he ups his hands to ask students to comeforward. Space and distance is the second nonverbal that’s more often thantouching in teaching learning process after hands. It used the teacher to explainhis material in the used space and distance the teacher stands up in front of astudents to explains his material, touching is nonverbal used the teacher inteaching learning process, touching used the teacher to communication with astudent’s while the teacher asks a students to come forward if the students didn’twant to come forward the teacher stand up beside a students and be touches theirbody. Chronemics was rarely used by the teacher in the classroom, chonemicsused the teacher while he gives task to the students he gives limed the time to thestudents to prepare the material that would be presentation. Beside that the effectof nonverbal communication used were helping students understanding andaccompanying to verbal message. Helping students understanding more easily toa students to receive the material that’s explains by the teacher. Accompanying toverbal message is a student’s more easily understand to get the point of teachers’explanation in teaching learning process.